Happiness, morality, and freedom - Melnick, Arthur (Studies in moral philosophy., 2014)
To be happy is to be satisfied with one's life according to a standard that one can claim as a reasonable being. Being moral and being held morally responsible are shown to be essential to being happy in this sense.